Evaluating the benefit of adjuvant radiotherapy after extensive lymph node dissection for gastric cancer: a single-institute retrospective study - Yu-Nong Wang; Shou-Yi Chang; Jing-Min Hwang; You-Kang Chang; Woei-Yau Kao; Hsiang-Lin Wan; I-Shiang Tzeng; Chao-Chuan Wu (Tzu Chi Medical Journal)
Objective: This study aimed to evaluate whether adjuvant radiotherapy (RT) can improve the treatment outcome of patients with locally advanced gastric cancer who underwent extensive lymph node dissection (ELND). Materials and Methods: This retrospective study included patients with gastric cancer pathological stages IIA–IIIC at Taipei Tzu Chi Hospital between 2008 and 2015. Patients (a) aged >80 years, (b) with distant metastasis at diagnosis, (c) with coexisting malignancies, (d) who did not complete the prescribed RT course, and (e) who died 1 month after surgery were excluded. Among 420 patients diagnosed with gastric cancer, 98 were included. Results: The median follow-up was 24.5 months. Of 39 patients who underwent adjuvant RT, 38 also received adjuvant chemotherapy (CT). Of 59 patients who did not receive adjuvant RT, only 34 received adjuvant CT. ELND was performed in 67.3% of the patients. The 5-year overall survival (OS) rate was 40%. In the univariate analyses, adjuvant CT regimen, 5-fluorouracil + leucovorin, was associated with worst outcome, while TS-1 was associated with better survival outcome (P = 0.018). The number of involved lymph nodes was strongly related to the OS and disease-free survival (DFS) (P < 0.001). We tried using different numbers of involved lymph nodes as a cutoff point and found that adjuvant RT significantly improved both OS and DFS in patients whose involved lymph nodes were ≥4 (OS, P = 0.017; DFS, P = 0.015). In multivariate analyses, better DFS was associated with negative surgical margin (P = 0.04), earlier disease stage (P = 0.001), adjuvant radiotherapy (P = 0.045), and adjuvant CT regimen TS-1 (P = 0.001). Conclusion: Adjuvant RT could improve DFS of patients with locally advanced gastric cancer with or without ELND. When the number of involved lymph nodes is ≥4, adjuvant RT is strongly suggested.